Novel Quinazolin-2,4-Dione Hybrid Molecules as Possible Inhibitors Against Malaria: Synthesis and in silico Molecular Docking Studies - Haredi Abdelmonsef, Aboubakr; Eldeeb Mohamed, Mahmoud; El-Naggar, Mohamed; Temairk, Hussain; Mohamed Mosallam, Ahmed (Frontiers in Molecular Biosciences, 2020)
The research explores the synthesis of a series of novel hybrid quinazolin-2,4-dione analogues bearing acetyl/amide bridged-Nitrogen heterocyclic moieties such as azetidinone, pyrrole, oxazole, oxadiazole, thiazole, pyrazole, and thiazolidine scaffolds 2-16. The newly synthesized compounds were structurally confirmed by IR, 1H-NMR, 13C-NMR, MS and elemental analysis. In addition, an in silico molecular docking analysis of new compounds and standard drug (Chloroquine) has been performed to analyze the binding modes of interaction to the putative active site of Plasmodium falciparum Dihydroorotate dehydrogenase (pfDHODH). Aiming to search for potentially better antimalarials, a modern approach has been undertaken to identify new quinazolin-2,4-dione derivatives targeting pfDHODH. The identification antimalarial activity of the newly synthesized compounds by using experimental techniques is expensive and requires extensive pains and labor. The compound 11 showed the highest binding affinity against pfDHODH. Further, the pharmacokinetic properties (ADMET) of the prepared compounds are predicted through in silico technique.